Pascua, a Yaqui village in Arizona - Spicer, Edward Holland, 1906-1983 (University of Arizona Press, 1984)
A portrait of the Yaqui Indian village of Pascua, located on the outskirts of Tucson, Arizona, outlines the village's history, economics, customs of kinship, and complex religious ceremonial organization and practices.